2021
DOI: 10.1155/2021/5567001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Alpha Testing of EzHifz Application: Al-Quran Memorization Tool

Abstract: Learning to memorize the Quran presents a challenge. This paper reports the development and alpha testing of a mobile application called “EzHifz” for Quran memorization based on the VARK learning style. The application received positive feedback for user acceptance testing and heuristic testing. The Fleiss kappa coefficient (κ) results for user acceptance testing show a very good level of agreement (κ = 0.850). Heuristic testing results show that κ = 0.731 for content, manual guide, memorization activities, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…For instance, a mobile application is a simple and effective way to memorize Quran, and 90% of the Quranmemorizing students thought the app was helpful in Quranic memorization (Safar, 2017) With the looping method, these current programs may show the text and replay the reciter's audio. Some programs include audio recording and memorizing performance management (Mustafa et al, 2021). Mustafa et al (2021) researched integrating visual (V), auditory (A), All the participants agreed that giving students the option of remembering the Quran using the VARK learning style will provide them with more learning alternatives and allow them to use the program more effectively.…”
Section: Students In Pahangmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a mobile application is a simple and effective way to memorize Quran, and 90% of the Quranmemorizing students thought the app was helpful in Quranic memorization (Safar, 2017) With the looping method, these current programs may show the text and replay the reciter's audio. Some programs include audio recording and memorizing performance management (Mustafa et al, 2021). Mustafa et al (2021) researched integrating visual (V), auditory (A), All the participants agreed that giving students the option of remembering the Quran using the VARK learning style will provide them with more learning alternatives and allow them to use the program more effectively.…”
Section: Students In Pahangmentioning
confidence: 99%
“…Some programs include audio recording and memorizing performance management (Mustafa et al, 2021). Mustafa et al (2021) researched integrating visual (V), auditory (A), All the participants agreed that giving students the option of remembering the Quran using the VARK learning style will provide them with more learning alternatives and allow them to use the program more effectively. It was found that the VARK learning style could be integrated with memorizing techniques based on the evaluation results.…”
Section: Students In Pahangmentioning
confidence: 99%
“…Hasil ini menunjukkan tingkat persetujuan yang baik, yang menunjukkan bahwa aplikasi EzHifz memenuhi persyaratan desain dan pengembangan berdasarkan atribut yang dievaluasi. [7]…”
Section: Penelitian Terkaitunclassified
“…In addition, the A-ba-ha-ta method teaches reading and writing the al-Qur'an and focuses on phonology (pronunciation of hijaiyah letters) (Arifin, Retnawati, Mailool, & Putranta, 2020;Mohd Yusoff, Raja Yusof, & Ibrahim, 2020;Senan, Wan Ab Aziz, Othman, & Suparjoh, 2017). The Ezhifz application which was developed based on learning styles is able to create effective learning to memorize the al-Qur'an and can increase learning motivation in inquiry learning (Mustafa, Mohd Zaki, Mohamad, Basri, & Ariffin, 2021).…”
Section: Introductionmentioning
confidence: 99%